Augmented Reality Books: Motivation, Attitudes, and Behaviors of Young Readers - Roumba, Evanthia; Nicolaidou, Iolie (My University, 2022)
Augmented Reality (AR) books show potential to increase young learners’ reading motivation, which is important given children’s declining reading motivation over the school years. Previous studies measured reading motivation only in higher education and only after users’ experience with AR. Few empirical studies focused on primary education children and those examined attitudes, not motivation. This study aimed to: a) examine how young children’s motivation changes through the experience of reading AR books and b) document their attitudes and behaviors after this experience. The theoretical framework was based on Keller’s ARCS model of motivation. Participants in this pre-test post-test case study were 40 fourth and fifth graders. Data sources included validated questionnaires and an observation protocol of children’s behavior while interacting with AR books. Children’s motivation had a statistically significant increase in attention (t39 = –3.07, p < 0.01), confidence (t39 = –2.44, p < 0.05) and satisfaction (t39 = –3.26, p < 0.01). Children showed a high level of enthusiasm with AR technology when interacting with the first AR book, which notably decreased with the second book. The children maintained positive attitudes and behaviors towards AR. The study showed that even through short-term interactions, AR books have the potential to increase young students’ reading motivation. It adds to our knowledge concerning the use of AR books by primary school children, who are under-represented in the literature. Directions for future research are drawn
Keywords: primary school; young children; Augmented Reality; reading motivation; attitudes; behaviors